Simple and Effective Load Volume Estimation in Moving Trucks using LiDARs - Amorim, Lucas L.; Mutz, Filipe; Badue, Claudine; de Souza, Alberto; Oliveira-Santos, Thiago (Anais da Conference on Graphics, Patterns and Images (SIBGRAPI); 2019: Anais da XXXII Conference on Graphics, Patterns and Images, 2019)
Industries need to track the amount of materialsand goods transported through processing units in order tooptimize production. In large-scale industries, trucks and trainsare commonly used for transportation. The manual evaluationof the volume of material being transported by these vehiclescan be imprecise, inefficient, and even unsafe for employees.Therefore, this work presents an automated system for estimatingthe volume of load in moving trucks using a pair of multi-layerlight detection and ranging (LiDAR) sensors. The sensors aremounted in a structure so that trucks can pass through withoutstopping. The proposed system can be used with any type ofcompact load such as grains, and powders. A mesh of the load isbuilt and used for estimating the volume. A simple, efficient, andeffective heuristic is proposed for tracking the truck’s positions.The system was deployed and evaluated in a mining company inreal conditions of operation. Experimental results indicate thatthe system produces accurate estimates of the volume of orepowder transported by trucks. The reconstruction of the loadsand the estimative of their volumes are performed once the datais acquired and lasts less than 1.5 minutes on average.